Hepatitis E virus is the leading cause of acute viral hepatitis in Lothian, Scotland. (March 2016) - Kokki, I.; Smith, D.; Simmonds, P.; Ramalingam, S.; Wellington, L.; Willocks, L.; Johannessen, I.; Harvala, H.
Abstract: Acute viral hepatitis affects all ages worldwide. Hepatitis E virus (HEV) is increasingly recognized as a major cause of acute hepatitis in Europe. Because knowledge of its characteristics is limited, we conducted a retrospective study to outline demographic and clinical features of acute HEV in comparison to hepatitis A, B and C in Lothian over 28 months (January 2012 to April 2014). A total of 3204 blood samples from patients with suspected acute hepatitis were screened for hepatitis A, B and C virus; 913 of these samples were also screened for HEV. Demographic and clinical information on patients with positive samples was gathered from electronic patient records. Confirmed HEV samples were genotyped. Of 82 patients with confirmed viral hepatitis, 48 (59%) had acute HEV. These patients were older than those infected by hepatitis A, B or C viruses, were more often male and typically presented with jaundice, nausea, vomiting and/or malaise. Most HEV cases (70%) had eaten pork or game meat in the few months before infection, and 14 HEV patients (29%) had a recent history of foreign travel. The majority of samples were HEV genotype 3 (27/30, 90%); three were genotype 1. Acute HEV infection is currently the predominant cause of acute viral hepatitis in Lothian and presents clinically in older men. Most of these infections are autochthonous, and further studies confirming the sources of infection (i.e. food or blood transfusion) are required.